Peningkatan Kemampuan Membaca Suku Kata Siswa Kelas I Melalui Permainan Kartu Huruf di SDN No. 61/VII Bukit Marau I Kec. Singkut - Andri Saputra; Jasman Saputra; Irdian Beni Saputra; Hasrudi Adinata (Jurnal Ilmiah Wahana Pendidikan, 2026)
Reading is a fundamental skill for elementary school students, yet many first-grade students still experience difficulties in reading syllables. This classroom action research aimed to improve students’ syllable reading ability through the use of letter card games at SD Negeri No.61/VII Bukit Marau I. The study was conducted in two cycles involving planning, action, observation, and reflection, with 20 first-grade students as participants. Data were collected through observations and reading tests. The results showed an improvement in teacher and student activities as well as students’ learning outcomes, with learning mastery increasing from 35% in the pre-cycle to 55% in Cycle I and reaching 100% in Cycle II. These findings indicate that letter card games are effective in improving the syllable reading ability of first-grade elementary school students.